Combined Orthodontic And Surgical Correction Of An Adolescent Patient With Thin Palatal Cortex And Vertical Maxillary Excess - Hedge, Manjunath; Hedge, C; Parajuli, U; Kamath, P (Kathmandu University Medical Journal, 2013)
This paper describes the treatment of a male patient aged 14 years who presented with a skeletal class I, vertical maxillary excess, marked increase in overjet, thin palatal cortex and a gummy smile. Considering the severity of his malocclusion and its impact severity on his psychosocial well being, he was managed with a combined approach of Fixed Orthodontic therapy and Orthognathic surgery, even though his growth was not complete. Records of Pre treatment, Post treatment and three years in retention were analyzed and the functional and esthetic results were found to be fairly stable. Kathmandu University Medical Journal | VOL.10 | NO. 3 | ISSUE 39 | JUL- SEP 2012 | Page 88-92 DOI: http://dx.doi.org/10.3126/kumj.v10i3.8029